2017
DOI: 10.1371/journal.pone.0188362
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the type of training task on intermanual transfer effects in upper-limb prosthesis training: A randomized pre-posttest study

Abstract: Intermanual transfer, the transfer of motor skills from the trained hand to the untrained hand, can be used to train upper limb prosthesis skills. The aim of this study was to determine the relation between the magnitude of the intermanual transfer effect and the type of training task. The used tasks were based on different aspects of prosthetic handling: reaching, grasping, grip-force production and functional tasks. A single-blinded clinical trial, with a pre-posttest design was executed. Seventy-one able-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This holds for elite athletes, but it is also true for recreational sports and also has implications for rehabilitation. In rehabilitation, the transfer of motor skills from the trained to the untrained arm can be useful in the therapy of brain-lesioned patients [1] or in upper-limb prosthesis training [24].…”
Section: Introductionmentioning
confidence: 99%
“…This holds for elite athletes, but it is also true for recreational sports and also has implications for rehabilitation. In rehabilitation, the transfer of motor skills from the trained to the untrained arm can be useful in the therapy of brain-lesioned patients [1] or in upper-limb prosthesis training [24].…”
Section: Introductionmentioning
confidence: 99%
“… 14 Additionally, intermanual transfer training can be used to train prosthetic limbs in people with amputation. 15 Individuals with amputated upper or lower limbs often start learning prosthetic skills after getting the prosthesis. However, they could start the prosthetic training immediately after the amputation using the intermanual transfer, so that training of the unaffected limb could enhance the prosthetic skills of the affected limb.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is also known as intermanual transfer of training. 15 Motor learning is a continuous process, which starts with an acquisition of a task and progresses with the transfer of the task. 16 Previous studies have suggested that variability in task and strength training could facilitate the intermanual transfer of motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…There are good reasons for studying the generalization of motor learning from one arm to the other, untrained arm. On a behavioral level, understanding the mechanisms of intermanual transfer can help athletes and coaches design effective training measures (Haaland & Hoff, 2003) or it can be useful in upper-limb prosthesis training (Romkema et al, 2017). On a neuronal level, the study of intermanual transfer can broaden our knowledge about hemispheric interactions (Chase & Seidler, 2008) or it can unveil both the global and the local nature of internal representations of motor learning (Harris, 1963;Lefumat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%